Distribuição dos impactos de investimentos em construção civil no Nordeste: Programa Minha Casa Minha Vida - Vieira, Flávio de Oliveira (2013)
This dissertation consists in evaluating the results of the Programa Minha Casa Minha Vida – PMCMV, using the input-output model of inter-regional, in order to analyze the distribution of the economic impacts in final demand on total production, employment, wages and value added between the states of the Northeast and the rest of Brazil. To evaluate this phenomenon, will be using the values of investment planned by PMCMV for the Construction sector between 2009 and 2012 deflated by the National Index of Construction Costs Market - Internal Availability (INCC-DI) for December 2012. To calculate the impact on employment, the multiplier was deflated by the National Consumer Price Index (IPCA) also for December 2012. After analyzing the results, we conclude that the magnitude of the direct impact on the production in the northeastern states and in states from the rest of the country, in relation to participation in the GDP - Gross Domestic Product National, demonstrates a concern of the government reduce regional inequalities. However, considering that the structure and economics of the Northeast sector requires a strong interdependence of the rest of Brazil, parts of the initial investments end up being disposed of for other states resulting in a spillover effect of wealth scheduled.